MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN ALAT PERAGA PADA MATERI GEOMETRI RUANG - Situmorang, Rya Uli; Sopia, Nurapni (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2020)
The purpose of this study was to determine the factors that cause the low student learning outcomes in space geometry material, describe the use of teaching aids in improving learning outcomes in space geometry material. As well as knowing the increase in learning outcomes in students geometry space by using teaching aids. This is attempted to overcome the problem of low student learning outcomes and have not yet reached the Minimum Mastery Learning Standards (SKBM). The method used in this paper is a quantitative method by looking at student learning outcomes obtained from direct experience in the use of teaching aids on building materials in class XA SMAN 2 Sekadau and supported by literature studies. There are two factors that cause the low student learning outcomes, namely: (1) internal factors include physiological and psychological, and (2) external factors include family, school, and community. Based on the results of research on the use of cube frame props can improve student learning outcomes in class X SMAN 2 Sekadau on geometry material space (determine the distance between points, points to lines, and points to the field) by 29.2% and achieve completeness classically by 88, 4%.